Timbang Besarnya Manfaat dari Salah Sasar Penerima Bantuan Iuran Jaminan Kesehatan - Soewondo, Prastuti (UI Scholars Hub, 2017)
One of the foremost government policies implemented in achieving Universal Health Coverage for the Indonesian population is the provision of financial assistance through contribution of Social Health Insurance for 92.4 million targeted poor and near poor households. This segment of the population is referred to as Penerima Bantuan Iuran (PBI) and represents about 35% of the total population. This study reveals the government’s progress in protecting the health of this sub-population. The data is derived from the 2016 National Social Economic Survey. The results indicate that, at the national level, the government’s health protection program has reached the majority of poor and near poor household (51%), especially those residing in Eastern part of the country (58%). Together with local government’s support, 59.5% of poor and near poor households (66.4% in Eastern region) have been insured. While improvements in coverage should still be top policy agenda, this achievement of the government deserves more appreciation. We show that misallocation of PBI to wealthy households is only small (3%), yet often broadcasted with much hype to create agitation